Computer-aided vaccine design - Chuan, Tong Joo; Ranganathan, Shoba (Woodhead Publishing series in biomedicine, 2013)
Computational pre-screening of antigens is now routinely applied to the discovery of vaccine candidates. Computer-aided vaccine design is a comprehensive introduction to this exciting field of study. The book is intended to be a textbook for researchers and for courses in bioinformatics, as well as a laboratory reference guide. It is written mainly for biologists who want to understand the current methods of computer-aided vaccine design. The contents are designed to help biologists appreciate the underlying concepts and algorithms used, as well as limitations of the methods and strategies for their use.